BREAKING THE LABEL: DEVELOPMENT OF ULTRA-PROCESSED-FOOD INTERACTIVE EDUCATIONAL VIDEO TO IMPROVE NUTRITION LITERACY AND HEALTHY FOOD SELECTION IN STUDENTS - Valentina Wiyanda Ratu Pratikno; Zahra Anggita Pratiwi; Agung Wibowo; Aprinia Dian Nurhayati (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Consumption Ultra-Processed Food (UPF) in students is classified as high as 50.3%, although as many as 48% of students have good UPF knowledge and 61.7% of students have the habit of reading food labels. This shows that good knowledge is not always directly proportional to healthy food consumption patterns. This research aims to develop interactive educational videos